Prevalence of depression, anxiety and Quality of life among North Indian Polycystic ovary syndrome Women: Evidence from a prospective observational study - Habib, Sana; Anwar, Arifa; Hoda, Farazul; Verma, Rishabh; Akhtar, M.; Najmi, Abul Kalam (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Polycystic ovary syndrome (PCOS) is a common heterogeneous gynaecological endocrine disorder characterized by clinical features including oligo-amenorrhea/ovulatory dysfunction, hyperandrogenism and polycystic ovarian morphology. PCOS increases the risk of depression and anxiety which leads to poor quality of life. Aim of the study were to determine the prevalence of anxiety and depression among women suffering from PCOS and to determine the quality of life (QOL) in PCOS women. Methods: The study was prospective, observational, non-interventional and questionnaire-based. 192 women with PCOS voluntarily helped in filling the questionnaires consisting of questions using PHQ-9 for depression, GAD-7 for anxiety, SF-12 for general health and PCOSQ-50 for disease-specific domains. All data were recorded in pre-designed case record forms and analysis of data was done using different statistical methods. Results: Majority of PCOS women were either overweight or obese. Based on PHQ-9 20% of women was suffering with major depression and based on GAD-7, 25% with major anxiety. It is found that psychosocial and emotional domain and coping domain of PCOSQ-50 is significant in patients with major depression and major anxiety. Significant effects were seen on their general health as per SF-12 domain. Lack of physical exercise was found in 83% of women. Conclusions: PCOS is a complex disease which decreases the overall quality of life. Therefore, treatment of PCOS women should include psychological counselling along-with with medication, especially in obese PCOS women. Women should be educated with the benefits of lifestyle modification in PCOS.